ANALISIS PENGARUH KEPEMILIKAN PEMERINTAH, KEPEMILIKAN ASING, RISIKO LIKUIDITAS DAN RISIKO KREDIT TERHADAP KINERJA KEUANGAN BANK - Sabrina, Farah Nur; Muharam, Harjum (Diponegoro Journal of Management, 2015)
This study aims to analyze the effect of different types of ownership, liquidity risk and credit risk on bank financial  performance.  State ownership  and foreign ownersip  were used as the ownership indicators. Liquid Asset to Total Asset (LATA), Non Performing Loan (NPL) and Return On Asset (ROA) ratio were used as the proxied of liquidity risk, credit risk and financial performance. The Population that was used in this research consisted of all conventional  commercial  banks which published the financial statements during 2007-2011. After passed the purposive sampling method there were 51 banks obtained as samples. The data analysis technique used is descriptive statistic, panel regression test with common effect model, classical assumption test and hypotheses test. The result  of this  research  showed  that  independent  variable  consisted  of state  ownership,  foreign ownership,  LATA,  NPL  and  control  variable  bank  size  all  have  significant  impact  on  ROA. Research also found that state banks and foreign banks have a better level of profitability  than private domestic banks.